Groundwater recharge assessment in the upper Limpopo River basin: a case study in Ramotswa dolomitic aquifer - Baqa, Simamkele Siyambonga (My University, 2017)
Hydrogeological research was undertaken in the transboundary Ramotswa dolomitic aquifer to provide understanding and quantification of the processes governing recharge mechanism and rates, in order to promote efficient and sustainable groundwater resource utilization and development, as well as to improve the Ramotswa transboundary aquifer management. Hydrochemical and tracer approaches were utilized to evaluate the processes governing the recharge mechanism while the chloride mass balance approach was further applied to assess groundwater recharge rates. Results indicated that all groundwater samples contained detectable amounts of tritium highlighting the renewability of the transboundary Ramotswa aquifer resources. Two distinct water types were characterised: sub-modern waters approximately recharge prior to the 1950s and a mixture of modern and sub-modern waters of recently recharge rainfall indicative of active recharge in the area through intensive rainfall. Correlation between δ18O and δ2H, and soil Cl- indicated that groundwater recharge in the Ramotswa dolomitic aquifer takes place mainly by two flow mechanisms: a displacement of moisture through a diffuse or piston flow through permeable soils and from concentrated runoffs due to surface depressions, and a preferential flow component through fractures that outcrop at surface and riverbed infiltration along the ephemeral Notwane River. Annual groundwater recharge estimates varied from 0.4% MAP to 12% MAP and from 5% MAP to 14% MAP within the northern parts and the southern parts of the study area, respectively. Recharge estimates correlated well with the proposed mechanism of flow both in the southern and in the northern parts of the study area as well as with the previous studies conducted within the greater Ramotswa area. A way forward to ensure the long-term sustainability of the transboundary Ramotswa aquifer resources is recommended, such as to preserve and protect potential recharge areas through carefully controlled land use planning and development, and to equate abstraction rates to average recharge rates, which has to be subjected to the Limpopo Watercourse Commission.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Hydrogeology. July 2017.
Keywords: Groundwater recharge--South Africa; Limpopo River